Judicial Oversight of the International Court of Justice over the Actions of the United Nations: Between the Absence of Text and the Requirements of International Legitimacy: An Analytical Study in Light of the Rules of International Law (Al-Farooq Journal of Sciences, 2026)
This study analyzes the judicial oversight of the International Court of Justice over United Nations actions in the absence of an explicit legal provision granting it direct supervisory authority. The study adopts analytical, descriptive, and critical approaches by examining the Court’s contentious and advisory jurisdiction, the legal views supporting and rejecting judicial oversight, and the impact of its absence on the legitimacy of Security Council and General Assembly decisions. The study concludes that judicial oversight is an important safeguard for international legality and recommends expanding advisory opinions, requiring reasoned international decisions, and activating subsequent legal review.
Keywords: judicial oversight, International Court of Justice, United Nations, Security Council, international legality, international law